The Anatolian Journal of Cardiology 2022
DOI: 10.5152/anatoljcardiol.2021.190
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic performance of Controlling Nutritional Status score in patients with ST segment elevation myocardial infarction treated with primary percutaneous coronary intervention

Abstract: Objective: The effect of malnutrition in patients with ST segment elevation myocardial infarction (STEMI) is not fully understood. In this study, we tried to investigate the prognostic consequence of the Controlling Nutritional Status (CONUT) score in patients with STEMI. Methods: In this study, we evaluated the CONUT scores of 1,028 patients with STEMI and examined its relationship with major adverse cardiovascular events (MACE) (all-cause mortality, myocardial reinfarction, and vessel revascularization) duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…In this study, patients with moderate and severe malnutrition had more CKD than those with normal or mild malnutrition (Table S1), consistent with the findings of a previous study [12]. However, previous studies on the association between malnutrition and ACS prognosis included relatively young patients in their late 50 s and 60 s [13,14]. Meanwhile, the average age of the patients in this study was approximately 70 years, which reflects the age of many Japanese patients undergoing PCI [15,16].…”
Section: Discussionsupporting
confidence: 90%
“…In this study, patients with moderate and severe malnutrition had more CKD than those with normal or mild malnutrition (Table S1), consistent with the findings of a previous study [12]. However, previous studies on the association between malnutrition and ACS prognosis included relatively young patients in their late 50 s and 60 s [13,14]. Meanwhile, the average age of the patients in this study was approximately 70 years, which reflects the age of many Japanese patients undergoing PCI [15,16].…”
Section: Discussionsupporting
confidence: 90%
“…This difference may partially be due to reduced mortality factors in similar studies, such as Killip classification, DM, and HT. 11,27 Likewise, we found that age, Killip class, hemoglobin, creatinine, LMCA stenosis, LVEF, and NPS were independent determinants of mortality among STEMI patients who underwent primary PCI. Besides, previous studies have shown that high CRP levels are associated with an increased incidence of in-hospital and long-term adverse outcomes in AMI patients.…”
Section: Discussionmentioning
confidence: 69%
“…8,9 Current studies have reported that a variety of inflammation-or nutrition-related indicators, such as the prognostic nutritional index (PNI), controlling nutritional status (CONUT), C-reactive protein (CRP)/albumin ratio, systemic inflammation score (SII), platelet to lymphocyte ratio (PLR), neutrophil to lymphocyte ratio (NLR), Glasgow prognostic score (GPS) and lymphocyte to monocyte ratio (LMR), might be related to outcomes in STEMI patients. [10][11][12][13][14][15] Nevertheless, these markers are still insufficient, and the results are controversial. Thus, more consistent, comprehensive, and effective risk assessment algorithms for STEMI patients are still required.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study demonstrated that 20% of overweight or obese patients with ST-segment elevation myocardial infarction had malnutrition. 20 This shows that malnutrition does not only occur in patients with a low BMI. Previous research has held the viewpoint that the severity of malnutrition in IBD patients is related to disease extent.…”
Section: Discussionmentioning
confidence: 91%